2015
DOI: 10.1093/aob/mcv076
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of Trxo1 increases the viability of tobacco BY-2 cells under H2O2treatment

Abstract: A decreased content of endogenous H2O2 may be responsible in part for the delayed cell death found in over-expressing cells, in which changes in oxidative parameters and antioxidants were less extended after the oxidative treatment. It is concluded that PsTrxo1 transformation protects TBY-2 cells from exogenous H2O2, thus increasing their viability via a process in which not only antioxidants but also Trxo1 seem to be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…However, in yeast trx1/trx2 double mutants, an increase in glutathione content (mainly GSSG) has been reported (Muller ). This putative compensation has been also observed when the gene expression of two TRX h was shown to increase in GSH‐deficient mutants (Schnaubelt et al ) or in Tobacco BY‐2 cells over‐expressing Ps TRX o 1 presenting lower levels of GSH than non‐over‐expressing cells (Ortiz‐Espín et al , Calderón et al ). From a physiological point of view, the glutathione redox state could be more influential in explaining the effects of different stresses, in the control of gene expression and protein function (Gómez et al , Rellán‐Alvarez et al , Schnaubelt et al ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, in yeast trx1/trx2 double mutants, an increase in glutathione content (mainly GSSG) has been reported (Muller ). This putative compensation has been also observed when the gene expression of two TRX h was shown to increase in GSH‐deficient mutants (Schnaubelt et al ) or in Tobacco BY‐2 cells over‐expressing Ps TRX o 1 presenting lower levels of GSH than non‐over‐expressing cells (Ortiz‐Espín et al , Calderón et al ). From a physiological point of view, the glutathione redox state could be more influential in explaining the effects of different stresses, in the control of gene expression and protein function (Gómez et al , Rellán‐Alvarez et al , Schnaubelt et al ).…”
Section: Discussionmentioning
confidence: 65%
“…The induction of the activity was correlated with the increase in the capacity of AOX, as well as a higher demand to regenerate the oxidized form of PRXIIF (Martí et al ), probably influencing the higher levels of H 2 O 2 found in our KO mutants under salinity. Furthermore, higher amount of TRX o 1 in Pstrxo1 over‐expressing tobacco BY‐2 cells protected them against induced oxidative stress by exogenous H 2 O 2 treatment, increasing some antioxidant enzyme activities and their viability (Ortiz‐Espín et al ), pointing TRX o 1 as a key component in the defense against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-qPCR was performed on a 7500 Real Time PCR System (Applied Biosystems, USA) with SYBR Green Supermix (Bio-Rad, Madrid, Spain) [23]. Each reaction was performed in triplicate.…”
Section: Quantitative Real Time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…PRXs can decrease the level of mitochondrial H 2 O 2 using reduced TRX or GSH as reductant sources, which in turn are reduced by thioredoxin reductase and GR [62]. At-PRXII F is one of six types II PRX identified in the genome of Arabidopsis and the only PRX that is targeted to the plant mitochondrion, which is essential for redox homeostasis by the decomposition of peroxides and by playing role in protecting the mitochondria during pathogen infection [62,70].…”
Section: Mitochondria-associated Ros Metabolism and Non-ros Moleculesmentioning
confidence: 99%